Clinical anaesthesia : lecture notes - Gwinnutt, Carl L. (Wiley-Blackwell, 2012)
Perfect for medical students, junior doctors, anaesthetic nurses and allied health professionals, Lecture Notes Clinical Anaesthesia provides a thorough introduction to the modern principles and practices of clinical anaesthesia